Impedimetric microbial sensor for real-time monitoring of phage infection of Escherichia coli - Cheng, Ming Soon (2016)
We describe an impedimetric microbial sensor for real-time monitoring of the non-lytic M13 bacteriophage infection of Escherichia coli cells using a gold electrode covalently grafted with a monolayer of lipopolysaccharide specific antibody. After infection, damage to the lipopolysaccharide layer on the outer membrane of E. coli causes changes to its surface charge and morphology, resulting in the aggregation of redox probe, Fe(CN)63−/4− at the electrode surface and thereby increases its electron-transfer rate. This consequent decrease of electron-transfer resistance in the presence of bacteriophage can be easily monitored using Faradaic impedance spectroscopy. Non-lytic bacterium–phage interaction which is hardly observable using conventional microscopic methods is detected within 3 h using this impedimetric microbial sensor which demonstrates its excellent performance in terms of analysis time, ease and reduced reliance on labeling steps during in-situ monitoring of the phage infection process.